Mobilisations féministes pendant les années 1970 à Rennes, un mouvement particulier ? - Lydie Porée (Les Cahiers de Framespa)
First focusing on Paris, historical awareness of second-wave feminist mobilisations in France has grown to look beyond the French capital. These movements have been researched in Rennes, the capital of Brittany. Women’s groups and organisations in favour of the liberalization of abortion were active in the city in the 1970s. Comparing them to groups in other French cities, does the feminist movement in Rennes reveal any specificities? The question especially arises when it comes to sources, the scope of which vary greatly according to the groups studied. In Rennes, mobilisations in favour of the liberalization of abortion were signicantly divided. As for women’s groups, they did not necessarily correspond to the way Parisian feminists viewed women’s groups outside Paris.